Clinical Outcomes of Closing- and Opening-Wedge High Tibial Osteotomy for Treatment of Anteromedial Unicompartmental Knee Osteoarthritis - Lu, Jiangfeng; Tang, Shiyu; Wang, Yanru; Li, Yao; Liu, Chang; Niu, Yingzhen; Cao, Pengkai; Wang, Fei (The Journal of Knee Surgery, 2019)
This article compares the long-term outcomes of closing-wedge osteotomy (CWO) and opening-wedge osteotomy (OWO) in the treatment of unicompartmental medial osteoarthritis with varus deformity. This study included 79 patients who underwent high tibial osteotomy (HTO) between 2002 and 2008. Pre- and postoperative radiography and computed tomography were used to evaluate the posterior tibial slope, the patellar height, the tibiofemoral angle, and the lateral and medial tibiofemoral joint space. Pre- and postoperative severity of arthritis was assessed with the Kellgren–Lawrence grading system. Pre- and postoperative American Knee Society (AKS) score and Lysholm Knee Score (LKS) were determined to evaluate functional outcomes. The duration of follow-up was 86.1 ± 6.2 months. Postoperatively, at the most recent follow-up, there was a slight increase in the size of the medial tibiofemoral joint space after CWO and OWO, which reflected a decrease in stress on the medial compartment and manifested as a significant improvement in the AKS knee and function scores and the LKS. OWO increased the posterior tibial slope as compared with the preoperative value, while CWO reduced the posterior tibial slope. CWO and OWO for HTO resulted in similar functional outcomes. OWO was associated with patella infera and more severe patellofemoral arthritis, while CWO was associated with a greater severity of lateral tibiofemoral arthritis.
Keywords: high tibial osteotomy; lateral closing-wedge osteotomy; medial opening-wedge osteotomy; osteoarthritis; patellofemoral arthritis